SACRECTOMY ASSOCIATED WITH VERTEBRECTOMY: A NEW TECHNIQUE USING DOWEL GRAFTS FROM CADAVERS - Araújo, Thiego Pedro Freitas (Acta Ortop Bras, 2018)
OBJECTIVE: The purpose of this study was to demonstrate, in a case series, a new sacrectomy technique using an iliac crest dowel graft from a cadaver. STUDY DESIGN: Report of a case series with description of a new surgical technique. METHODS: The technique uses four bars to support the posterior spine and a dowel graft in the iliac wings, with compression of the spine and pelvis above it, to support the anterior spine. Three cases were operated on, and in all of them, a vertebrectomy was used. RESULTS: In the first two cases, the technique was performed as a two-stage surgery. The first stage was performed via the anterior and peritoneal access routes, and the second stage via the posterior access route. In the third case, retroperitoneal access via the anterior route meant that the technique could be performed in one stage, resulting in an overall reduction in surgical time (1250 vs. 1750 vs. 990 minutes, respectively). CONCLUSION: The new technique enables fixation with biomechanical stability, which is essential to support the stress in the lumbosacral transition and promote earlier rehabilitation. Level of evidence IV, case series.